2009
DOI: 10.1002/jcp.21706
|View full text |Cite
|
Sign up to set email alerts
|

Transforming growth factor‐beta 1 (TGF‐β1) induces angiogenesis through vascular endothelial growth factor (VEGF)‐mediated apoptosis

Abstract: VEGF and TGF‐β1 induce angiogenesis but have opposing effects on endothelial cells. VEGF protects endothelial cells from apoptosis; TGF‐β1 induces apoptosis. We have previously shown that VEGF/VEGF receptor‐2 (VEGFR2) signaling mediates TGF‐β1 induction of apoptosis. This finding raised an important question: Does this mechanism stimulate or inhibit angiogenesis? Here we report that VEGF‐mediated apoptosis is required for TGF‐β1 induction of angiogenesis. In vitro the apoptotic effect of TGF‐β1 on endothelial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
156
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 286 publications
(166 citation statements)
references
References 62 publications
(101 reference statements)
7
156
1
Order By: Relevance
“…While we cannot rule out AT1-mediated effects of losartan, we show that brain exposure to losartan indeed blocked TGF-β signaling, and reduced albumin-induced increase in p-Smad2/3 levels as well as astrocytic activation. As TGF-β1 was also shown to induce the activation of vascular endothelial growth factor (VEGF) signaling 53,54 , losartan may also prevent angiogenesis and BBB dysfunction- both known to contribute to the epileptogenic process 55,56 . These findings, along with reports that losartan decreases BBB permeability in hypertensive rats 57,58 , raise the possibility of a direct effect of losartan on endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…While we cannot rule out AT1-mediated effects of losartan, we show that brain exposure to losartan indeed blocked TGF-β signaling, and reduced albumin-induced increase in p-Smad2/3 levels as well as astrocytic activation. As TGF-β1 was also shown to induce the activation of vascular endothelial growth factor (VEGF) signaling 53,54 , losartan may also prevent angiogenesis and BBB dysfunction- both known to contribute to the epileptogenic process 55,56 . These findings, along with reports that losartan decreases BBB permeability in hypertensive rats 57,58 , raise the possibility of a direct effect of losartan on endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Besides being a pro-fibrogenic cytokine, TGF-β has the ability to promote angiogenesis. VEGF and TGF-β interact closely with respect to angiogenic and fibrogenic effects (Ferrari et al, 2009). A recent in vitro study showed that SWCNT-induced fibroblast proliferation and collagen production is mediated by VEGF and TGF-β1 (Azad et al, 2012).…”
Section: Biological Activities Cntsmentioning
confidence: 99%
“…Further, in vitro approaches can leverage the epitope of sequestering to design bioactive substrates that promote EC pro-angiogenic function. For example, during angiogenesis, VEGF elicits a pro-angiogenic response 181 whereas high levels of TGF-β1 can inhibit angiogenesis 182,183 . Thus, surfaces that can simultaneously up-regulate VEGF activity (via allosteric sequestering) and down-regulate TGF-β1 activity (via active site sequestering) could, in principle, promote EC pro-angiogenic function at the sequestering interface.…”
Section: Introductionmentioning
confidence: 99%